Update to the knowledge of the social wasps of the Brazilian state of Amapá based on the vespid collection of the Amapá Research Institute (IEPA) (Hymenoptera, Vespidae, Polistinae) - Silveira, Orlando Tobias; Furtado, Nercy Virginia Rabelo; Gama, José Madson De Freitas; de Seixas Felizardo, Sherlem Patricia; Dos Santos, Ian Patrick Vilhena (Zootaxa, 2019)
Information is presented concerning specimen records of polistine social wasps in the state of Amapá, Brazil, in the years from 1904 to 2016, mainly coming from the IEPA and MPEG collections. Spatial distribution of records and of the total collecting effort were analyzed with respect to general landscape aspects of the region, such as vegetation types, hydrography, road infrastructure and the state network of conservation unities. The number of social wasp species registered for Amapá is now 144, with 17 new records of species for the Guiana Shield, and nine species not yet described. Seventeen genera are known to occur in the region, with Mischocyttarus de Saussure and Polybia Lepeletier being richer in species.